Beyond the Doctrine of Man : Decolonial Visions of the Human. - Drexler-Dreis, Joseph (Fordham University Press, 2019)
The essays in this volume interrogate the problem of modern/colonial definitions of the human person and take up the struggle to decolonize such descriptions. Contributions engage work from various fields, including ethnic studies, religious studies, theology, queer theory, philosophy, and literary studies.